A virtual adaptive RC damper control method to suppress voltage oscillation in DC microgrid. (March 2023) - Kumar, Ranjan; Bhende, C.N.
Highlights: A new virtual adaptive RC Damper Control Method is proposed. The proposed method allows for the easy setting of the control parameters. The load converter's dynamic performance is unaffected. It is Highly Robust during Sudden Changes- Input Voltage and load changes. Voltage fluctuation is modest with a short recovery time than the existing method. Abstract: In DC Microgrid tightly regulated load converters operate as a constant power load (CPL). CPLs have negative incremental resistance characteristics, which leads to voltage oscillations and instability in DC microgrid systems. As a result, a virtual adaptive resistance–capacitance (VARC) damper control mechanism has been developed in this study to overcome the instability impact generated by the CPL. To satisfy the need for system stability, a technique to insert a virtual R-C connected in parallel with the capacitor (located on the feeder-side converter) is proposed. The proposed active damping control is self-adaptive for variations in load current. The proposed method allows for a straightforward setting of the control parameters, in which the dynamic performance of the load converter was unaltered. Stability is provided by an inherent and accurate adaptive control technique, as well as by strong resilience during sudden changes in input voltage and CPL plug-and-play. Both of these factors contribute to high levels of robustness. Therefore, practical restrictions such as weight reduction and low power dissipation, which are essential for onboard DC MGs, are maintained. The simulation results are carried out and the effectiveness of the proposed technique is tested by considering various operating conditions. Furthermore, the proposed technique is compared with the existing methods and it is found to be superior under various operating conditions.